Atomic mechanisms and diffusion anisotropy of Cu tetramers on Cu(111) - Ferron, Julio (2014)
The surface diffusion of compact Cu tetramers on Cu(111) has been studied at the atomic scale by means of molecular dynamics simulations using embedded atom interatomic potentials. The Cu clusters diffuse by several different mechanisms; all of them have the common trait of involving concerted displacements of at least some of the atoms forming the island. The anisotropy in the rhombus shape of the Cu tetramers and the different activation energies of the translational and rotational jumps result in highly anisotropic diffusion, with a transition from practically one-dimensional motion at low temperature to nearly isotropical two-dimensional random walk at high temperature. The use of molecular dynamics allows us to also determine the preexponential factors for each jump mechanism, from which analysis we can obtain some insight into their basic nature and the relationships between them.